2018
DOI: 10.1002/adbi.201800127
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Synthesis of Quasi‐Pyramidal CuInS2–ZnS Nanocrystals for Enhanced Near‐Infrared Targeted Fluorescent Imaging of Subcutaneous Melanoma

Abstract: Near‐infrared (NIR) fluorescent CuInS2–ZnS nanocrystals (CIZS NCs) are synthesized via an ultra‐fast, non‐injection microwave (MW)‐assisted nanoalloying process at 230 ºC within 5 min using 1‐dodecanethiol (DDT) as both the sulfur source and solvent under solvothermal (ST) condition. The structural and surface analyses reveal that DDT‐functionalized CIZS NCs exhibit quasi‐pyramids of tetragonal‐phase with well‐defined facets. The DDT‐functionalized CIZS NCs present a photoluminescence quantum yield (PLQY) of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 57 publications
(74 reference statements)
1
12
0
Order By: Relevance
“…Due to the high polarity of the (112) plane in the CIS tetragonal phase, the surface energy increased and grew very fast along the [112] direction. Similar results were observed by Chetty et al [51].…”
Section: Continuous Flow Reactorssupporting
confidence: 92%
“…Due to the high polarity of the (112) plane in the CIS tetragonal phase, the surface energy increased and grew very fast along the [112] direction. Similar results were observed by Chetty et al [51].…”
Section: Continuous Flow Reactorssupporting
confidence: 92%
“…28 The ex vivo imaging of the major organs and the tumor confirmed the NIR-fluorescence signal in the upper lobe of the lungs because of transient pulmonary trapping, slightly in the liver because of the enhanced permeability and retention (EPR) effect, and enhanced NIR- h because of elimination from mice. 24,25 The biodistribution of CIS-ZMGS NCs was confirmed by ex vivo imaging and ICP−MS analysis. Our results corroborated the recent studies on Gd-chelate-entrapped MSCs for detection of an early tumor (∼3 mm 3 ) using 4.7 T MR and optical imaging in 2 h by Kim et al 12 Also, the tumor homing ability of peptide-conjugated nanophosphor-labeled adiposederived stem cells (ASCs) in 24 h post-injection in a 4T1 tumor-bearing mice model was reported by Wu et al 49 However, the result concluded minimal tropism of ASCs in the 4T1 tumor owing to early sequestration by phagocytes in lung capillaries in contrast to accumulation in the liver.…”
Section: Resultsmentioning
confidence: 87%
“…However, further increase in reaction temperature resulted in destabilization and aggregation of surface-functionalized 1-DDT ligands, resulting in a drastic quenching in emission of MW-R synthesized NCs. 24 Despite effective capping of 1-DDT ligands on the NCs surface, there exist surface-related defects because of a high surface/volume ratio that facilitates nonradiative recombinations. Hence, the cation exchange or nanoalloying of ZnS was utilized to eliminate the surface defects and increase the confinement of electrons and holes in NCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations